Environment-Stable CoxNiy Encapsulation in Stacked Porous Carbon Nanosheets for Enhanced Microwave Absorption - Liang, Xiaohui; Man, Zengming; Quan, Bin; Zheng, Jing; Gu, Weihua; Zhang, Zhu; Ji, Guangbin (Nano-Micro Letters, 2020)
Magnetic/dielectric@porous carbon composites, derived from metal–organic frameworks (MOFs) with adjustable composition ratio, have attracted wide attention due to their unique magnetoelectric properties. In addition, MOFs-derived porous carbon-based materials can meet the needs of lightweight feature. This paper reports a simple process for synthesizing stacked CoxNiy@C nanosheets derived from CoxNiy-MOFs nanosheets with multiple interfaces, which is good to the microwave response. The CoxNiy@C with controllable composition can be obtained by adjusting the ratio of Co2+ and Ni2+. It is supposed that the increased Co content is benefit to the dielectric and magnetic loss. Additionally, the bandwidth of CoNi@C nanosheets can take up almost the whole Ku band. Moreover, this composite has better environmental stability in air, which characteristic provides a sustainable potential for the practical application. Highlights: 1 The microwave absorbing performance of alloy@C composites can be controlled through regulating ratio of metal ions. 2 Carbon-based alloy@C composites exhibit the potential stability of microwave absorption with almost the whole Ku band for the practical application.